PROSES DAN MAKNA RITUAL BUDAYA KASEBU - ruslin ruslin (Universitas Halu Oleo (UHO), 2023)
Kasebu traditional rituals are traditions that continue to be sustainable in the midst of the times while still running in accordance with the process that has been taught by the ancestors. This paper aims to describe and analyze the process and symbols of the implementation of Kasebu traditional rituals. This study used a qualitative descriptive approach. Data collection techniques include observation, interviews and documentation. The results of this study show that the process and symbols of implementing the Kasebu tradition are: (1) the recitation of prayers (podula) with the symbol of nine gutters containing food prepared by traditional leaders (kamokulano liwu). (2) Saare is a movement performed by a man dressed in traditional female clothes surrounded by a group of children with drum dance movements (po'toge). (3) Potumbu ritual, which is a morning ritual with freestyle physical competition in a field that has been determined following existing rules. (4) Desese oe mata is a ritual carried out by cleaning the spring water used as a water source requirement for the Wasilomata community. (5) Fomani, namely village silat performed by individuals and groups accompanied by large drums (ganda kapaso). (6) Double Kabueno as a closing ritual of Kasebu, which is the swing of drums from midnight to morning with the accompaniment of a certain Linda dance. In conclusion, the ritual process of Kasebu culture consists of the recitation of prayers (Podula), saare, Potumbu rituals, Fomani, and Kabueno Ganda.